Time-Course of Motor Involvement in Literal and Metaphoric Action Sentence Processing: A TMS Study - Reilly, Megan; Howerton, Olivia; Desai, Rutvik H. (Frontiers in Psychology, 2019)
There is evidence that the motor cortex is involved in reading sentences containing an action verb ("The lengthy spike was hammered into the ground") as well as metaphoric sentences ("The weak army was hammered again in battle"). Verbs such as 'hammered' may be homonyms, with separate meanings belonging to the literal action and metaphoric action, or they may be polysemous, with the metaphoric sense grounded in the literal sense. We investigated the time course of the effects of single-pulse transcranial magnetic stimulation to primary motor cortex on literal and metaphoric sentence comprehension. Stimulation 300 ms post-verb presentation impaired comprehension of both literal and metaphoric sentences, supporting a causal role of sensory-motor areas in comprehension. Results suggest that the literal meaning of an action verb remains activated during metaphor comprehension, even after the temporal window of homonym disambiguation. This suggests that such verbs are polysemous, and both senses are related and grounded in motor cortex.